The MIGRATION AS AN INVASION and THE COMMON EUROPEAN HOUSE Metaphors in media discourse - Mersina Mujagić (ExELL (Explorations in English Language and Linguistics))
The article discusses figurative use of expressions from the domains of INVASION and HOUSE in media discourse on the European migrant crisis. The conceptual metaphors MI-GRATION AS AN INVASION and the COMMON EUROPEAN HOUSE, which are inextricably relat-ed in the segments of the real discourse on migration, have strong rhetorical power and serve as a means of promoting antimigrant ideologies. The aim of this paper is to identify the instances of deliberate use of the aforementioned metaphors in British and Bosnian-Herzegovinian papers and describe their use in the media with the aim of changing address-ees’ perspectives on an important issue such as migration.